2018
DOI: 10.3390/ijerph15061220
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emissions in China’s Construction Industry: Calculations, Factors and Regions

Abstract: The production of construction projects is carbon-intensive and interrelated to multiple other industries that provide related materials and services. Thus, the calculations of carbon emissions are relatively complex, and the consideration of other factors becomes necessary, especially in China, which has a massive land area and regions with greatly uneven development. To improve the accuracy of the calculations and illustrate the impacts of the various factors at the provincial level in the construction indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…The major methods to identify the determinants of carbon emissions in the construction industry are the index decomposition analysis (IDA) and the structural decomposition analysis (SDA). The IDA has a wider application than the SDA for its flexibility and lower data requirement [10,[16][17][18]. However, the IDA only focuses on the direct effect and ignores the effect of the indirect energy demand and final demand [1,19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The major methods to identify the determinants of carbon emissions in the construction industry are the index decomposition analysis (IDA) and the structural decomposition analysis (SDA). The IDA has a wider application than the SDA for its flexibility and lower data requirement [10,[16][17][18]. However, the IDA only focuses on the direct effect and ignores the effect of the indirect energy demand and final demand [1,19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies paid little attention to the spatial spillover effects when examining the determinants of carbon emissions in the construction industry [1,[16][17][18]. They assumed that the studied regions were spatially independent from each other, and the characteristics of one region would not affect the carbon emissions of its neighboring regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has some characteristics: (1) Heterogeneity is when the individual agent is depicted with characteristics and attributes [22]. (2) Adaptivity is when the external environment changes, different agents conduct different adjustment behaviors to better adapt themselves to these changes of environment [23]. (3) Learnability is when each agent is rational, but the learning ability is different.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It became the world's largest carbon emitter in 2006, and was responsible for 64.8% of the increase in global carbon emissions between 2007 and 2012. Moreover, in 2013, carbon emissions of China approximately made up 28.6% of the world's total carbon emissions [2,3]. As China is facing great pressure from the international community on the issue of carbon emissions, the government is making an effort to control the carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the theory of multivariate distribution has been applied in many fields [10][11][12][13][14][15][16]. Many application examples have also shown that the design parameters derived from a joint probability distribution can better meet the design need of ocean engineering [17][18][19][20], reduce the building cost of ocean engineering more reasonably, explore return periods of multivariable waves, and calculate joint design level values more accurately. Additionally, all of these are of great significance for the design and risk management of related projects [21].…”
Section: Introductionmentioning
confidence: 99%